Barley protein concentrates: Extraction, structural and functional properties. (15th July 2018) - Houde, Marika; Khodaei, Nastaran; Benkerroum, Noreddine; Karboune, Salwa
Highlights: Alkaline and multi-enzymatic approaches were explored for barley protein extraction. A tri-enzymatic approach led to the highest protein recovery yield. Alkaline and tri-enzymatic approaches were rich in globulin and hordein, respectively. Concentrates showed emulsifying capacities comparable to whey protein isolate (WPI). Abstract: Protein concentrates were prepared from defatted barley ( Hordeum vulgare L.) flour using alkaline and enzymatic treatments. Milder enzymatic treatments included (i) a bi-enzymatic method involving the use of starch-hydrolyzing enzymes, and (ii) a tri-enzymatic method using the former bi-enzymatic treatment followed by digestion with glucanase. The concentrate obtained through alkaline extraction (AI-BP) was comprised mainly of low molecular weight fractions of proteins. Bi-enzymatic treatment produced a protein concentrate with the highest protein content (49.0%), while those obtained by the tri-enzymatic treatment followed by an isoelectric precipitation step (TEI-BP) gave the highest protein recovery yield (78.3%). In both of the latter concentrates, 35 kDa B-hordeins were the major protein fraction. Divergence in secondary/tertiary structure elements (AI-BP; TEI-BP) was obtained and attributed to the difference in the protein profiles. Further characterization of protein concentrates indicated that they exhibit pseudoplastic behavior. Emulsifying capacity of concentrates was comparable to that of whey protein isolate.